Polyzwitterionic hydrogel as well as preparation method and application thereof
Through the redox autocatalytic polymerization reaction under oxygen-free conditions, silver ions and persulfate ions are used to generate free radicals, solving the problem of preparing zwitterionic hydrogels without the help of external energy, achieving rapid and controllable polymerization in a wide temperature domain, and broadening the monomer concentration range.
Patent Information
- Application Number
- CN202411343300.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to prepare zwitterionic hydrogels within a wide monomer concentration range by radical polymerization without the use of external energy input such as light and heat.
By carrying out redox autocatalytic polymerization under oxygen-free conditions, free radicals are generated by the redox reaction between silver ions and persulfate ions, promoting the polymerization and cross-linking of zwitterionic monomers to form a hydrogel network.
It realizes the rapid and controllable preparation of polyzwitterionic hydrogels in a wide temperature range without the need for external energy input, which broadens the applicable concentration range of zwitterionic monomers and improves the simplicity and operability of the process.
Smart Images

Figure CN119775485A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogels, and in particular to a polyzwitterion hydrogel and a preparation method and application thereof. Background Art
[0002] Zwitterionic monomers are monomer molecules with both positive and negative charged functional groups in their molecular structure. This unique molecular structure gives them excellent hydrophilicity and biocompatibility. Zwitterionic hydrogels are mainly prepared by chemical crosslinking of water-soluble zwitterionic monomers and are widely used in medicine, bioengineering and other fields. When zwitterionic monomers are dissolved in deionized water, water molecules wrap around the zwitterionic molecular chains through hydrogen bonds and electrostatic interactions, making them dissolved and stable. However, additional steric barriers will also be formed, which will affect the polymerization of zwitterionic monomers. Therefore, a higher monomer concentration is currently required to prepare zwitterionic hydrogels.
[0003] Free radical polymerization is a commonly used method for preparing hydrogel materials. It mainly stimulates the decomposition of initiators to produce free radicals through external energy input such as light and heat, which triggers monomer polymerization and forms a three-dimensional cross-linked network structure. How to prepare zwitterionic hydrogel materials through free radical polymerization without the input of external energy such as light and heat, and within a wide range of monomer concentrations, is of great research value. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a polyzwitterionic hydrogel and a preparation method and application thereof. The preparation method provided by the present invention can achieve polymerization of zwitterionic monomers in a wide concentration range without the input of external energy such as light and heat.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a polyzwitterion hydrogel, comprising the following steps:
[0007] The hydrogel precursor solution is subjected to a redox autocatalytic polymerization reaction under anaerobic conditions to obtain a polyzwitterionic hydrogel; the hydrogel precursor solution comprises: a zwitterionic monomer, a crosslinking agent, polyvinyl alcohol, a water-soluble silver ion source, an initiator and water; the mass ratio of the zwitterionic monomer to water is 1:1 to 350.
[0008] Preferably, the zwitterionic monomer includes one or more of 2-methacryloyloxyethyl phosphorylcholine, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, 3-[(3-acrylamidopropyl)dimethylammonium]propionate and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate.
[0009] Preferably, the crosslinking agent comprises N',N-methylenebisacrylamide and / or polyvinyl alcohol diacrylate.
[0010] Preferably, the mass ratio of the zwitterionic monomer to the cross-linking agent is 1:0.001-350.
[0011] Preferably, the mass ratio of the zwitterionic monomer to polyvinyl alcohol is 1:0.05-150.
[0012] Preferably, the mass ratio of the zwitterionic monomer to the water-soluble silver ion source is 1:0.01-35.
[0013] Preferably, the mass ratio of the zwitterionic monomer to the initiator is 1:0.001-350;
[0014] The initiator includes a persulfate.
[0015] Preferably, the temperature of the redox autocatalytic polymerization reaction is -5 to 37°C, and the time is 0.25 to 10 minutes.
[0016] The present invention also provides a polyzwitterion hydrogel prepared by the preparation method described in the above technical solution.
[0017] The present invention also provides the application of the polyzwitterion hydrogel described in the above technical solution in the medical field or bioengineering.
[0018] In the preparation method provided by the present invention, silver ions and persulfate ions (S2O8 2- ) between the silver ions and the persulfate ions, specifically, in the presence of an initiator, a redox reaction occurs between the silver ions and the persulfate ions, causing the persulfate to decompose and generate free radicals, which can react with the zwitterionic monomers to form active centers, and in the presence of a cross-linking agent, the active centers further undergo spontaneous polymerization reactions with the zwitterionic monomers and cross-link, ultimately forming a hydrogel network, and polyzwitterionic hydrogels can be obtained without the need for external energy input (such as light, heat, etc.). Moreover, polyvinyl alcohol in the hydrogel precursor solution, as a hydration shielding agent, can coat the zwitterionic monomers through electrostatic interactions, shielding the aggregation of most water molecules around the zwitterionic monomer molecular chains, and inducing the zwitterions to form hydration shielding aggregation monomers through dipole-dipole interactions, so that the zwitterionic monomer molecular chains at low concentrations can also react well with free radicals, greatly broadening the concentration range of zwitterionic monomers suitable for polymerization. Moreover, the preparation method provided by the present invention has simple process, strong operability, mild reaction conditions, and controllable polymerization time.
[0019] Moreover, the preparation method provided by the present invention can prepare polyzwitterionic hydrogel quickly (0.25 to 10 minutes) and controllably within a wide temperature range (-5 to 37° C.) without the need for external energy input.
[0020] The polyzwitterion hydrogel prepared by the invention has good lubricity and antibacterial properties, and has broad application prospects in the fields of medicine and bioengineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a comparison diagram of the friction force of the PVC catheter surface with and without the polyzwitterion hydrogel coating prepared in Example 1;
[0022] Figure 2 This is a graph showing the antibacterial performance test results of the polyzwitterionic hydrogel prepared in Example 1. DETAILED DESCRIPTION
[0023] The present invention provides a method for preparing a polyzwitterion hydrogel, comprising the following steps:
[0024] The hydrogel precursor solution is subjected to a redox autocatalytic polymerization reaction under anaerobic conditions to obtain a polyzwitterionic hydrogel; the hydrogel precursor solution comprises: a zwitterionic monomer, a crosslinking agent, polyvinyl alcohol, a water-soluble silver ion source, an initiator and water; the mass ratio of the zwitterionic monomer to water is 1:1 to 350.
[0025] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0026] In the present invention, the preparation method of the hydrogel precursor solution preferably includes the following steps: dissolving a crosslinking agent and a zwitterionic monomer in water to obtain a monomer-crosslinking agent mixed solution; mixing the monomer-crosslinking agent mixed solution with a polyvinyl alcohol aqueous solution, then mixing it with a water-soluble silver ion source, deoxygenating it, and then mixing it with an initiator to obtain a hydrogel precursor solution.
[0027] In the present invention, the zwitterionic monomer preferably includes one or more of 2-methacryloyloxyethyl phosphorylcholine (MPC), [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide (SBMA), 3-[(3-acrylamidopropyl)dimethylammonium]propionate (CBAA) and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate (CBMA).
[0028] In the present invention, the crosslinking agent preferably includes N', N-methylenebisacrylamide and / or polyvinyl alcohol diacrylate, and more preferably N', N-methylenebisacrylamide. Taking N', N-methylenebisacrylamide as an example, its two acrylamide groups react with free radicals in the polymerization process to form a crosslinking structure, and this crosslinking effect connects different polymer chains together to form a three-dimensional network structure.
[0029] In the present invention, the mass ratio of the zwitterionic monomer to the crosslinking agent is preferably 1:0.001-350, and in specific embodiments can be 1:0.005, 1:0.006, 1:0.01, 1:0.03, 1:0.05, 1:0.1, 1:0.5, 1:1, 1:10, 1:20, 1:50, 1:100, 1:150, 1:200, 1:250, 1:300 or 1:350.
[0030] In the present invention, the mass ratio of zwitterionic monomer to water in the monomer-crosslinking agent mixed solution is preferably 1:1 to 350, and in specific embodiments can be 1:1, 1:5, 1:10, 1:20, 1:50, 1:100, 1:150, 1:166.7, 1:200, 1:250, 1:300 or 1:350. In the present invention, the water preferably includes deionized water.
[0031] In the present invention, the mass ratio of the zwitterionic monomer to the polyvinyl alcohol in the polyvinyl alcohol aqueous solution is preferably 1:0.05-150, and in specific embodiments it can be 1:0.05, 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:16.7, 1:17, 1:18, 1:19, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140 or 1:150. In the present invention, the polyvinyl alcohol as a hydration shielding agent can form hydration shielding aggregated monomers by inducing aggregation between zwitterionic monomers at low concentrations, so that zwitterionic monomers can still be successfully polymerized at low concentrations to prepare polyzwitterionic hydrogels.
[0032] In the present invention, the concentration of the polyvinyl alcohol aqueous solution is preferably 5 to 30 wt%, and in a specific embodiment, it can be 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt% or 30 wt%. In the present invention, the polyvinyl alcohol aqueous solution is preferably obtained by dissolving polyvinyl alcohol in water. In the present invention, the dissolving temperature is preferably 70 to 100 ° C, and in a specific embodiment, it can be 70 ° C, 75 ° C, 80 ° C, 85 ° C, 90 ° C, 95 ° C, 98 ° C or 100 ° C. In the present invention, the water preferably includes deionized water. After the dissolution, the present invention preferably also includes cooling the obtained solution to room temperature to obtain a polyvinyl alcohol aqueous solution.
[0033] In the present invention, the water-soluble silver ion source preferably includes one or more of silver nitrate, silver fluorosilicate and silver chlorate, and is more preferably silver nitrate; the mass ratio of the zwitterionic monomer to the silver ion source is preferably 1:0.01-35, and in specific embodiments it can be 1:0.01, 1:0.04, 1:0.1, 1:0.2, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:6.7, 1:7, 1:8, 1:9, 1:10, 1:15, 1:20, 1:25, 1:30 or 1:35.
[0034] In the present invention, the deoxygenation preferably includes vacuum deoxygenation.
[0035] In the present invention, the mass ratio of the zwitterionic monomer to the initiator in the hydrogel precursor solution is preferably 1:0.001-350, and in specific embodiments can be 1:0.01, 1:0.012, 1:0.05, 1:0.06, 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:5, 1:10, 1:20, 1:50, 1:100, 1:150, 1:200, 1:250, 1:300 or 1:350. In the present invention, the initiator preferably includes persulfate, more preferably includes ammonium persulfate and / or potassium persulfate.
[0036] In the present invention, the mass ratio of the zwitterionic monomer to water in the hydrogel precursor solution is 1:1 to 350, and in specific embodiments it can be 1:1, 1:1.9, 1:2, 1:5, 1:9.5, 1:10, 1:20, 1:50, 1:100, 1:150, 1:200, 1:250, 1:300, 1:316.7, 1:320 or 1:350.
[0037] In the present invention, the temperature of the redox autocatalytic polymerization reaction is preferably -5 to 37°C, and in specific embodiments, it can be -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C or 37°C; the time of the redox autocatalytic polymerization reaction is preferably 0.25 to 10 min, and in specific embodiments, it can be 0.25 min, 0.3 min, 0.5 min, 0.7 min, 0.9 min, 1 min, 1.2 min, 1.5 min, 2 min, 2.5 min, 2.7 min, 3 min, 3.5 min, 3.9 min, 4 min, 4.5 min, 5 min, 5.5 min, 6 min, 6.5 min, 7 min, 7.5 min, 8 min, 8.5 min, 9 min, 9.3 min, 9.5 min or 10 min; during the redox autocatalytic polymerization reaction, silver ions and persulfate ions (S2O8 2- ) undergo a redox reaction, causing the persulfate to decompose and produce free radicals. The free radicals can react with the zwitterionic monomers to form active centers, which further undergo spontaneous polymerization and cross-linking with other zwitterionic monomers to eventually form a hydrogel network and obtain a hydrogel block.
[0038] The preparation method provided by the present invention realizes the rapid polymerization of a wide concentration of zwitterionic monomer aqueous solution (the mass ratio of zwitterionic monomer to water is 1:1 to 350) within a wide temperature range (-5 to 37°C) without the need for external energy input such as light and heat; and the controllable polymerization of polyzwitterionic hydrogel is achieved by controlling the dosage ratio of each raw material.
[0039] The present invention also provides a polyzwitterion hydrogel prepared by the preparation method described in the above technical solution.
[0040] The present invention also provides the application of the polyzwitterion hydrogel described in the above technical solution in the medical field or bioengineering. In the present invention, the application preferably includes the application as a lubricating coating on the surface of medical materials; the medical material preferably includes a medical catheter. The polyzwitterion hydrogel provided by the present invention has good lubricity, which can not only reduce the friction coefficient of the catheter surface, but also play a good antibacterial role, and is expected to be applied to biomedical technology fields such as the manufacture of lubricating coatings on the surface of medical materials.
[0041] In order to further illustrate the present invention, the polyzwitterion hydrogel provided by the present invention and its preparation method and application are described in detail below in conjunction with the examples, but they should not be construed as limiting the scope of protection of the present invention.
[0042] Example 1
[0043] Solution A: Dissolve 1 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 0.03 g of N',N-methylenebisacrylamide in 5 mL of deionized water.
[0044] Solution B: 0.5 g of polyvinyl alcohol was added to 4.5 mL of deionized water, and the mixture was heated at 98° C. to dissolve. After the solution was cooled, a 10 wt % polyvinyl alcohol aqueous solution was obtained.
[0045] After solution B and solution A were mixed, 0.2 g of AgNO3 was added, and after being fully dissolved, oxygen was removed by vacuum, and then 0.06 g of ammonium persulfate was added to obtain a hydrogel precursor solution.
[0046] The gelation time of the hydrogel precursor solution was evaluated by a rheometer. The test mode was an oscillation mode, the test temperature was 25°C, the test frequency was 1 Hz, and the test stress was 5 Pa. After testing, the gelation time (i.e., redox self-catalytic polymerization reaction) of the hydrogel precursor solution at a temperature of 25°C was 1.2 min, and a polyzwitterionic hydrogel was obtained after gelation.
[0047] Example 2
[0048] Solution A: 1 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 0.03 g of N',N-methylenebisacrylamide were dissolved in 5 mL of deionized water to obtain a zwitterionic monomer solution.
[0049] Solution B: 0.5 g of polyvinyl alcohol was added to 4.5 mL of deionized water, and the mixture was heated at 98° C. to dissolve. After the solution was cooled, a 10 wt % polyvinyl alcohol aqueous solution was obtained.
[0050] After solution B and solution A were mixed, 0.2 g of AgNO3 was added, and after complete dissolution, the mixture was deoxygenated under vacuum, followed by the addition of 0.06 g of ammonium persulfate.
[0051] The hydrogel precursor solution is subjected to a redox autocatalytic polymerization reaction (gelation) at 0° C. to obtain a polyzwitterionic hydrogel.
[0052] The gelation time of the hydrogel precursor solution was evaluated by a rheometer. The test mode was an oscillation mode, the test temperature was 0°C, the test frequency was 1 Hz, and the test stress was 5 Pa. After testing, the gelation time of the hydrogel precursor solution at a temperature of 0°C was 9.3 min, and a polyzwitterionic hydrogel was obtained after gelation.
[0053] Example 3
[0054] Solution A: 1 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 0.03 g of N',N-methylenebisacrylamide were dissolved in 5 mL of deionized water to obtain a zwitterionic monomer solution.
[0055] Solution B: 0.5 g of polyvinyl alcohol was added to 4.5 mL of deionized water, and the mixture was heated at 98° C. to dissolve. After the solution was cooled, a 10 wt % polyvinyl alcohol aqueous solution was obtained.
[0056] After solution B and solution A were mixed, 0.2 g of AgNO3 was added, and after complete dissolution, the mixture was deoxygenated under vacuum, followed by the addition of 0.06 g of ammonium persulfate.
[0057] The gelation time of the hydrogel precursor solution was evaluated by a rheometer. The test mode was an oscillation mode, the test temperature was 37°C, the test frequency was 1 Hz, and the test stress was 5 Pa. After testing, the gelation time of the hydrogel precursor solution at a temperature of 37°C was 0.7 min, and a polyzwitterionic hydrogel was obtained after gelation.
[0058] Example 4
[0059] Solution A: 0.03 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 0.03 g of N',N-methylenebisacrylamide were dissolved in 5 mL of deionized water to obtain a zwitterionic monomer solution.
[0060] Solution B: 0.5 g of polyvinyl alcohol was added to 4.5 mL of deionized water, and the mixture was heated at 98° C. to dissolve. After the solution was cooled, a 10 wt % polyvinyl alcohol aqueous solution was obtained.
[0061] After solution B and solution A were mixed, 0.2 g of AgNO3 was added, and after complete dissolution, the mixture was deoxygenated under vacuum, followed by the addition of 0.06 g of ammonium persulfate.
[0062] The gelation time of the hydrogel precursor solution was evaluated by a rheometer. The test mode was an oscillation mode, the test temperature was 25°C, the test frequency was 1 Hz, and the test stress was 5 Pa. After testing, the hydrogel precursor solution with a monomer concentration of 0.31 w / v% had a gelation time of 0.3 min at a temperature of 25°C, and a polyzwitterionic hydrogel was obtained after gelation.
[0063] Example 5
[0064] Solution A: 5 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 0.03 g of N',N-methylenebisacrylamide were dissolved in 5 mL of deionized water to obtain a zwitterionic monomer solution.
[0065] Solution B: 0.5 g of polyvinyl alcohol was added to 4.5 mL of deionized water, and the mixture was heated at 98° C. to dissolve. After the solution was cooled, a 10 wt % polyvinyl alcohol aqueous solution was obtained.
[0066] After solution B and solution A were mixed, 0.2 g of AgNO3 was added, and after complete dissolution, the mixture was deoxygenated under vacuum, followed by the addition of 0.06 g of ammonium persulfate.
[0067] The gelation time of the hydrogel precursor solution was evaluated by a rheometer. The test mode was an oscillation mode, the test temperature was 25°C, the test frequency was 1 Hz, and the test stress was 5 Pa. After testing, the gelation time of the hydrogel precursor solution with a monomer concentration of 52.63 w / v% at a temperature of 25°C was 0.9 min, and a polyzwitterionic hydrogel was obtained after gelation.
[0068] Example 6
[0069] Solution A: 1 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 0.03 g of N',N-methylenebisacrylamide were dissolved in 5 mL of deionized water to obtain a zwitterionic monomer solution.
[0070] Solution B: 0.5 g of polyvinyl alcohol was added to 4.5 mL of deionized water, and the mixture was heated at 98° C. to dissolve. After the solution was cooled, a 10 wt % polyvinyl alcohol aqueous solution was obtained.
[0071] After solution B and solution A were mixed, 0.1 g of AgNO3 was added, and after complete dissolution, the mixture was deoxygenated under vacuum, and then 0.02 g of ammonium persulfate was added.
[0072] The gelation time of the hydrogel precursor solution was evaluated by a rheometer. The test mode was an oscillation mode, the test temperature was 25°C, the test frequency was 1 Hz, and the test stress was 5 Pa. After testing, the gelation time of the hydrogel precursor solution with an initiator concentration of 0.21 w / v% at a temperature of 25°C was 3.9 min, and a polyzwitterionic hydrogel was obtained after gelation.
[0073] Example 7
[0074] Solution A: 1 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 0.03 g of N',N-methylenebisacrylamide were dissolved in 5 mL of deionized water to obtain a zwitterionic monomer solution.
[0075] Solution B: 0.5 g of polyvinyl alcohol was added to 4.5 mL of deionized water, and the mixture was heated at 98° C. to dissolve. After the solution was cooled, a 10 wt % polyvinyl alcohol aqueous solution was obtained.
[0076] After solution B and solution A were mixed, 0.1 g of AgNO3 was added, and after complete dissolution, the mixture was deoxygenated under vacuum, followed by the addition of 0.06 g of ammonium persulfate.
[0077] The gelation time of the hydrogel precursor solution was evaluated by a rheometer. The test mode was an oscillation mode, the test temperature was 25°C, the test frequency was 1 Hz, and the test stress was 5 Pa. After testing, the gelation time of the hydrogel precursor solution with an initiator concentration of 0.63 w / v% at a temperature of 25°C was 2.7 min, and a polyzwitterionic hydrogel was obtained after gelation.
[0078] Example 8
[0079] Solution A: 1 g of [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl)ammonium hydroxide and 0.03 g of N',N-methylenebisacrylamide were dissolved in 5 mL of deionized water to obtain a zwitterionic monomer solution.
[0080] Solution B: 0.5 g of polyvinyl alcohol was added to 4.5 mL of deionized water, and the mixture was heated at 98° C. to dissolve. After the solution was cooled, a 10 wt % polyvinyl alcohol aqueous solution was obtained.
[0081] After solution B and solution A were mixed, 0.1 g of AgNO3 was added, and after complete dissolution, the mixture was deoxygenated under vacuum, and then 0.1 g of ammonium persulfate was added.
[0082] The gelation time of the hydrogel precursor solution was evaluated by a rheometer. The test mode was an oscillation mode, the test temperature was 25°C, the test frequency was 1 Hz, and the test stress was 5 Pa. After testing, the gelation time of the hydrogel precursor solution containing 1.05 w / v% of initiator at a temperature of 25°C was 1.5 min, and a polyzwitterionic hydrogel was obtained after gelation.
[0083] Example 9
[0084] Solution A: 1 g of 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate and 0.03 g of N',N-methylenebisacrylamide were dissolved in 5 mL of deionized water to obtain a zwitterionic monomer solution.
[0085] Solution B: 0.5 g of polyvinyl alcohol was added to 4.5 mL of deionized water, and the mixture was heated at 98° C. to dissolve. After the solution was cooled, a 10 wt % polyvinyl alcohol aqueous solution was obtained.
[0086] After solution B and solution A were mixed, 0.2 g of AgNO3 was added, and after complete dissolution, the mixture was deoxygenated under vacuum, followed by the addition of 0.06 g of ammonium persulfate.
[0087] The gelation time of the hydrogel precursor solution was evaluated by a rheometer. The test mode was an oscillation mode, the test temperature was 25°C, the test frequency was 1 Hz, and the test stress was 5 Pa. After testing, the hydrogel precursor solution containing 10.53 w / v% of the monomer (3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate) had a gelation time of 1.5 min at a temperature of 25°C, and a polyzwitterionic hydrogel was obtained after gelation.
[0088] Example 10
[0089] Solution A: 1 g of 2-methacryloyloxyethyl phosphorylcholine and 0.03 g of N',N-methylenebisacrylamide were dissolved in 5 mL of deionized water to obtain a zwitterionic monomer solution.
[0090] Solution B: 0.5 g of polyvinyl alcohol was added to 4.5 mL of deionized water, and the mixture was heated at 98° C. to dissolve. After the solution was cooled, a 10 wt % polyvinyl alcohol aqueous solution was obtained.
[0091] After solution B and solution A were mixed, 0.2 g of AgNO3 was added, and after complete dissolution, the mixture was deoxygenated under vacuum, followed by the addition of 0.06 g of ammonium persulfate.
[0092] The gelation time of the hydrogel precursor solution was evaluated by a rheometer. The test mode was an oscillation mode, the test temperature was 25°C, the test frequency was 1 Hz, and the test stress was 5 Pa. After testing, the gelation time of the hydrogel precursor solution containing 10.53 w / v% of the monomer (2-methacryloyloxyethyl phosphorylcholine) at a temperature of 25°C was 2.5 min, and a polyzwitterionic hydrogel was obtained after gelation.
[0093] Test Example 1
[0094] The outer surface of the PVC medical catheter was polished and the polished area was thoroughly cleaned with deionized water. After cleaning, the catheter was immersed in the hydrogel precursor solution prepared in Example 1 and slowly pulled out from the hydrogel precursor solution, fixed at room temperature (polymerization reaction occurred at the same time) for 30 minutes to obtain a modified PVC medical catheter with outer surface coating. The modified PVC medical catheter was separated from the inner wall model under the action of tension using a universal material testing machine (stretching speed was 50 mm / min). During the stretching process, the stretching force was approximately equal to the friction force during relative motion. The results are shown in Table 1. Figure 1 , wherein Blank is an unmodified PVC medical catheter and Coating is a modified PVC medical catheter. It can be seen that compared with the unmodified PVC medical catheter, the PVC medical catheter modified by polyzwitterion hydrogel has smaller friction.
[0095] Test Example 2
[0096] Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa were selected to conduct antibacterial tests on the polyzwitterion hydrogel obtained in Example 1. The three bacterial solutions were diluted to 10% with LB liquid culture medium. 6 CFU / mL, evenly add 100μL of bacterial solution on the surface of the sterilized sample, place it in a 37℃ constant temperature incubator and culture it for 24h, then use 1mL of sterile PBS solution to elute the bacterial solution on the surface of the sample, and use sterile PBS solution to dilute the eluate ten times continuously, take 100μL of the dilution and evenly spread it on the LB solid culture medium, place it in a 37℃ constant temperature incubator and culture it for 18h, then take it out and take a picture, see Figure 2 , calculate the bacterial concentration according to formula 1, and calculate the antibacterial rate according to formula 2:
[0097] Bacterial concentration = colony count × dilution factor × 10 × 11 Formula 1;
[0098] Antibacterial rate = (1-concentration of bacterial solution in experimental group / concentration of bacterial solution in control group) × 100% Formula 2.
[0099] It can be seen that the bacterial concentrations of the three bacteria on the surface of the polyzwitterion hydrogel are all 0, and the antibacterial rates of the polyzwitterion hydrogel against the three bacteria are all 100%.
[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a polyzwitterionic hydrogel, comprising the following steps: The hydrogel precursor solution is subjected to a redox autocatalytic polymerization reaction under anaerobic conditions to obtain a polyzwitterionic hydrogel; the hydrogel precursor solution comprises: a zwitterionic monomer, a crosslinking agent, polyvinyl alcohol, a water-soluble silver ion source, an initiator and water; the mass ratio of the zwitterionic monomer to water is 1:1 to 350.
2. The preparation method according to claim 1, characterized in that: The zwitterionic monomer includes one or more of 2-methacryloyloxyethyl phosphorylcholine, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide, 3-[(3-acrylamidopropyl)dimethylammonium]propionate, and 3-[[2-(methacryloyloxy)ethyl]dimethylammonium]propionate.
3. The preparation method according to claim 1, characterized in that: The crosslinking agent includes N',N-methylenebisacrylamide and / or polyvinyl alcohol diacrylate.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The mass ratio of the zwitterionic monomer to the crosslinking agent is 1:0.001-350.
5. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the zwitterionic monomer to polyvinyl alcohol is 1:0.05-150.
6. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the zwitterionic monomer to the water-soluble silver ion source is 1:0.01-35.
7. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the zwitterionic monomer to the initiator is 1:0.001-350; The initiator includes a persulfate.
8. The preparation method according to any one of claims 1 to 3, characterized in that: The temperature of the redox autocatalytic polymerization reaction is -5 to 37° C., and the time is 0.25 to 10 minutes.
9. The polyzwitterionic hydrogel prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the polyzwitterionic hydrogel according to claim 9 in the medical field or bioengineering.
Citation Information
Patent Citations
Preparation method of high-flexibility amphoteric ionic hydrogel
CN105295073A
Nano-silver / dual-modified chitosan antibacterial hydrogel dressing for indicating wound infection condition through color change effect and preparation method of nano-silver / dual-modified chitosan antibacterial hydrogel dressing
CN113975458A
Cellulose normal-temperature reduction nano-silver and preparation method of self-polymerization functional hydrogel of cellulose normal-temperature reduction nano-silver
CN116813937A
Application of zwitterionic hydrogel in preparation of diabetes skin repair material
CN117599237A
Preparation method for synthesizing antibacterial hydrogel at room temperature
CN118184877A